Effect of the relationship between anemia and the threat of preterm labor in pregnant women at a peruvian hospital - Minaya Soto, Jerry Anibal (2022)
Objective. To determine the relationship between anemia and the threat of preterm birth in pregnant women at the Carlos Lanfranco La Hoz Hospital in the period 2020-2021. Materials and Methods. An observational, retrospective analytical case and control study was carried out in a population that consisted of all patients hospitalized in the gynecology and obstetrics service with a total population of 240, of which 120 pregnant women with preterm birth were cases and 120 with normal deliveries were controls. Results. The independent variable of anemia represented 36.7% of the total number of patients and the percentages of anemia with respect to the case groups was 48.3% and 28.3% in the controls, respectively. The multivariate analysis shows that anemia (OR: 2.24; CI: 95% 1.26-3.97; p:0.006) and insufficient prenatal controls (OR: 2.33; CI: 95% 1.32-4 .1; p:0.003) are significantly associated with the threat of preterm birth, adjusted to the variable’s history of premature birth, insufficient prenatal controls, age, obesity and being multi-pregnant. On the contrary, there was no significant association for the variables of obesity, history of preterm birth, age and multi-pregnancy. Conclusions. Having anemia and insufficient prenatal controls proved to be an important risk factor for developing threatened preterm birth.